PRENATAL YOGA AND IMPROVING MATERNAL HEALTH OUTCOMES: A LITERATURE REVIEW - Ni Nyoman Ayu Ningsih; Ni Wayan Armini; Ni Wayan Suarniti (Jurnal Endurance, 2026)
Pregnancy involves physical and psychological changes that may affect maternal health. Prenatal yoga, as a non-pharmacological intervention, has potential benefits in addressing these conditions. This study aimed to analyze the role of prenatal yoga in optimizing maternal health through a literature review. Articles were obtained from Google Scholar, PubMed, and ScienceDirect and analyzed descriptively. The results show that prenatal yoga effectively reduces anxiety, stress, and fear of childbirth, alleviates physical discomfort, and improves physiological conditions. It also has potential to improve pregnancy outcomes. In conclusion, prenatal yoga supports maternal health holistically and can be integrated into antenatal care.